Lost landscapes of an imaginary North and South (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
The introduction of computer programs for the generation of 3D landscapes eliminates the historical relationship with the referent. I establish parallelisms between the creation of the romantic landscape of the 19th century by the painters, together with the photographers who approach the subject of the sublime in the landscape from the origins of photography to the present day, and I submit them to a comparison with reality. generated through computer processes for the creation of landscapes and territories. These new synthetic and hyper-realistic realities replace the traditional way of relating to the landscape. The digital becomes incorporeal, questioning the testimony of the senses.
Keywords: Landscape; Generative Art; Photography; 3D